Heritability, Correlation, and Path Analysis on Various Characters of Tomato (Solanum lycopersicum) under Shading and Normal Condition - Ritonga, Arya Widura; Chozin, Muhamad Achmad; Syukur, Muhamad; Maharijaya, Awang; Sobir (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2019)
Character selection information is essential for plant breeding program. SSH3 tomato genotype (shade-loving genotype), 4974 (shade-sensitive genotype), and F2 population derived from “SSH3 x 4974” were evaluated to estimate the heritability, correlation, direct and indirect effects between yield and various yield atributting characters in tomato under shading and normal condition at Pasir Kuda Station, Bogor Agriculture University, West Java, Indonesia from July until October 2016. The results showed that plant height, leaf length, leaf width, leaf weight, specific leaf weight, fruit weight, fruit number per plant and fruit weight per plant had high heritability under normal condition, while plant height, fruit set, fruit number of plant and fruit weight per plant had high heritability under shading condition. High direct positive effect on yield per plant was resulted from fruit weight and fruit number of plant under shading and normal condition, while leaf width had direct positive effect on fruit weighr per plant only under shading condition. High indirect positive effect on yield per plant was resulted from fruit set, fruit length and fruit diameter under shading and normal condition, while plant heigh had high indirect effect on yield per plant only under shading condition. Fruit set, fruit weight, and fruit number per plant characters were potential to be used as character selection for tomato productivity in normal conditions. Plant height, fruit set and fruit number per plant were potential to be used as character selection for tomato productivity under shading condition. Keywords: direct effect, fruit set, indirect effect, low light tolerant